Indikasi Geografis atas Carica Dieng sebagai Strategi Penguatan Ekonomi Daerah - Ayup Suran Ningsih; Waspiah Waspiah; Selfira Salsabilla (Jurnal Suara Hukum, 2019)
Protection of the potential of regional products is a necessity for the region. An understanding of the importance of protecting Geographical Indications for policy makers in the regions is one of the efforts to protect the peculiarities of regional products. The specificity of the product of a region can be a regional economic strength when there is protection for Geographical Indications, because the product will increase its selling value. Regional economy is a series of economic activities carried out by local communities together in accordance with the potential of existing regions to fulfill their daily needs. Geographical indications are part of Intellectual Property which is currently a concern that was initiated by the Government to each region to map as well as to provide protection for regional products that have the potential to have geographical indications. Carica Dieng is a typical product that meets the requirements for geographical indications in accordance with Law Number 20 of 2016 concerning Trademarks and Geographical Indications and Government Regulation Number 51 of 2007 concerning Geographical Indications